THE USE OF CODE SWITCHING AS THE LANGUAGE CHOICE AMONG POLITICIANS. - Muh. Yahya Idris (PIP Makassar, 2018)
This research discussed about the use of code switching as the language choice among politicians.This research aimed to find out the types and functions of code switching used by politicians. This research focused on the types and functions of code switching based on the theory of types and functions of code switching by Appel and Muysken in 2006. Then, the data were analyzed using descriptive qualitative method.The researcher used note taking as the instrument to find out the valid data. This research was conducted in order to fiind the types and the functions of code-switching used by politicians in Satu Indonesia and Bicara 4 Mata program. The findings showed that there are two types and two functions of code switching used by politicians as language choice. The researcher concluded that the types of code-switching found in both sources are inter-sentential and intra-sentential code-switching and the functions of code-switching found in both data sources are referential function and expressive function.